Auditory training alters the physiological detection of stimulus-specific cues in humans - Tremblay, Kelly L. (2008)
OBJECTIVE: Auditory training alters neural activity in humans but it is unknown if these alterations are specific to the trained cue. The objective of this study was to determine if enhanced cortical activity was specific to the trained voice-onset-time (VOT) stimuli ‘mba’ and ’ba’, or whether it generalized to the control stimulus ‘a’ that did not contain the trained cue. METHODS: Thirteen adults were trained to identify a 10 ms VOT cue that differentiated the two experimental stimuli. We recorded event-related potentials (ERPs) evoked by three different speech sounds ‘ba’ ‘mba’ and ‘a’ before and after six days of VOT training. RESULTS: The P2 wave increased in amplitude after training for both control and experimental stimuli, but the effects differed between stimulus conditions. Whereas the effects of training on P2 amplitude were greatest in the left hemisphere for the trained stimuli, enhanced P2 activity was seen in both hemispheres for the control stimulus. In addition, subjects with enhanced pre-training N1 amplitudes were more responsive to training and showed the most perceptual improvement. CONCLUSION: Both stimulus-specific and general effects of training can be measured in humans. An individual’s pre-training N1 response might predict their capacity for improvement. SIGNIFICANCE: N1 and P2 responses can be used to examine physiological correlates of human auditory perceptual learning.